Self Disclosure pada Anggota Komunitas ATP - Siti Nabila Meiriskha; Yulianti (Bandung Conference Series: Communication Management, 2023)
Abstract. The community is a place for social interaction, both educational and non-educational. Researchers suspect that self-disclosure on social media or online networks, especially Instagram, is carried out for certain reasons or motives that make individuals more likely to express themselves on Instagram social media. Problems that arise on social media Instagram, in which there is a process of communication from within the individual as outlined in photos (status), videos, live Instagram, and Insta-stories. With this, the writer wants to know the self-disclosure of ATP members in using Instagram social media. Because in terms of self-disclosure it can also be realized not only by face-to-face communication, but can also be through the media or channels to be able to communicate it. This relates to the existence of self-disclosure in individuals. The theory used is the functional theory of self-disclosure by Derlega & Grzelak, 1979: Omarzu, 2000 which was developed for social media on the grounds that different social media capabilities activate different disclosure purposes, which in turn shape disclosure. The purpose of this study was to determine social legitimacy, expression, relationship development, identity clarification and social control on self-disclosure of Instagram social media users. The research method used in this study is to use descriptive quantitative research methods. The results of the research on self-disclosure of members of the ATP community on Instagram are disclosed in general, but on the dimension of social legitimacy for private employee work groups it is more open than the other dimensions, namely self-employed work and for the dimension of identity clarification for male and female gender groups both open, while in another dimension men are more open than women. Abstrak. Komunitas menjadi wadah untuk melakukan interaksi sosial baik bersifat edukasi maupun non edukasi. Peneliti menduga bahwa pengungkapan diri di media sosial atau jejaring online khususnya Instagram dilakukan karena ada alasan maupun motif – motif tertentu yang membuat individu lebih cenderung mengungkapkan dirinya di media sosial Intagram. Permasalahan yang muncul pada media sosial Instagram, didalamnya terdapat suatu proses komunikasi dari dalam diri individu yang dituangkan dalam foto (status), video, live Instagram, maupun Insta-stories. Dengan begitu penulis ingin mengetahui keterbukaan diri anggota ATP dalam menggunakan media sosial Instagram. Karena dalam hal keterbukaan diri dapat pula terwujud tidak hanya dengan komunikasi tatap muka, namun dapat pula melalui media atau saluran untuk dapat mengomunikasikannya. Hal ini berhubungan dengan adanya self disclosure pada individu. Teori yang digunakan adalah teori fungsional pengungkapan diri oleh Derlega & Grzelak, 1979: Omarzu, 2000 yang dikembangkan ke media sosial dengan alasan bahwa kemampuan media sosial berbeda mengaktifkan tujuan pengungkapannya yang berbeda, yang pada gilirannya membentuk pengungkapan. Tujuan dari penelitian ini adalah untuk mengetahui keabsahan sosial, ekspresi, perkembangan hubungan klarifikasi identitas dan kendali sosial pada self disclosure pengguna media sosial Instagram. Metode penelitian yang digunakan pada penelitian ini adalah adalah menggunakan metode penelitian kuantitatif deskriptif. Hasil penelitian Self disclosure anggota komunitas ATP di Instagram diungkapkan secara umum, namun pada dimensi keabsahan sosial untuk kelompok pekerjaan pegawai swasta lebih terbuka dari pada dimensi lain, yaitu pekerjaan wiraswasta dan untuk dimensi klarifikasi identitas untuk kelompok jenis kelamin laki-laki dan perempuan sama-sama terbuka, sedangkan dimensi lain laki – laki lebih terbuka dari pada perempuan.